The Spanish Case for Europe. The Power of Cultural Identity - Gonzalo Navajas (Studies in 20th & 21st Century Literature, 2009)
Europe has not been for Spain an easily assumed identity, a home within which Spaniards could find accommodation. Yet, for the first time in modern history, Spain has become fully integrated in the political and economic system of Europe and it functions within it as a strong and dedicated partner. Paradoxically, this new order has developed simultaneously with the increasing assertion of the local nationalities. I propose that the current political and cultural situation in both Europe and Spain has created the appropriate conditions for an extensive reexamination of the conventional European/Spanish paradigm. That is so because the circumstances on both ends of the relation have changed and, for the first time, both sides not only desire but they need the reconstruction and redefinition of a relation that has been destructive for both parts. What Francisco José de Goya, Julián Sanz del Río, and Manuel Azaña, among others, conceived as a nearly impossible and illusory task can now become a reality. From Francisco Zurbarán, El Greco and Pedro Calderón de la Barca to Federico García Lorca, Luis Buñuel and Pablo Picasso, the various manifestations of its culture have been Spain’s unquestioned achievement. This cultural continuum is the most promising entryway for Spain in the Heimat of Europe. I also propose that the issue of the various historical nationalities within Spain can be approached from the perspective of what Andrzej Stasiuk calls the “private histories” of the minorities of Europe. In the last part of the article, I study Spain’s transcontinental identity. Without ignoring the legitimate issues raised by private narratives, I suggest that the country’s full insertion in the global reality and its immersion in realities that are beyond its own will lead to the contextualization of the internal national divide and the emergence of new and more productive approaches towards its resolution.
Keywords: Spanish history; Europe; cultural identity; new order; Spanish/ European paradigm; assimilation; reconstruction; Goya; Sanz del Ría; Azaña; Zurbabám; El Greco; Pedro Calderón de la Barca García Lorca; Buñuel; Picasso; Heimat